Geriatric oncology in the Netherlands: a survey of medical oncology specialists and oncology nursing specialists. (6th April 2014) - Jonker, J.M.; Smorenburg, C.H.; Schiphorst, A.H.; van Rixtel, B.; Portielje, J.E.A.; Hamaker, M.E.
<x xml:space="preserve">Abstract</x> To identify ways to improve cancer care for older patients, we set out to examine how older patients in the Netherlands are currently being evaluated prior to oncological treatment and to explore the potential obstacles in the incorporation of a geriatric evaluation, using a web‐based survey sent to Dutch medical oncology specialists and oncology nursing specialists. The response rate was 34% (183 out of 544). Two‐thirds of respondents reported that a geriatric evaluation was being used, although primarily on an ad hoc basis only. Most respondents expressed a desire for a routine evaluation or more intensive collaboration with the geriatrician and 86% of respondents who were not using a geriatric evaluation expressed their interest to do so. The most important obstacles were a lack of time or personnel and insufficient availability of a geriatrician to perform the assessment. Thus, over 30% of oncology professionals in the Netherlands express an interest in geriatric oncology. Important obstacles to a routine implementation of a geriatric evaluation are a lack of time, or insufficient availability of geriatricians; this could be overcome with policies that acknowledge that quality cancer care for older patients requires the investment of time and personnel.